Fishes of lakes, rivers & oceans : based on the television series Wild, wild world of animals - Dozier, Thomas A.; Time-Life Television ([New York] : Time-Life Films, 1978)
Discusses fishes inhabiting lakes, rivers, estuaries, coastal waters, and the deep sea.
A Time-Life Television book; consultants, C. L. Smith, J. W. Atz.
Includes index.
Keywords: Peixes